WHITE WOOD PLANTS AS A SOURCE OF IDEAS FOR CREATING BATIK MOTIFS IN CASUAL CLOTHING - Dyta Lisnasari; Aan Sudarwanto (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2025)
This fashion work has the theme of Eucalyptus Plants as a Source of Ideas for Creating Batik Motifs in Casual Clothing. The source of inspiration for the eucalyptus plant comes from the surrounding environment because it has many properties needed by the local community. So with this work the author wants to bring and introduce to the general public through fashion trends. The aim of this work is to create a eucalyptus plant batik motif and apply it to casual clothing. The method used in the process of creating this work uses three stages, namely exploration, design, realization. The exploration stage is a step of observing the surrounding environment, social media, literature study and conducting data mining through interviews. The second stage is designing the motif by using all the data as a reference for making alternative sketches into the selected design. The third stage is the embodiment technique which realizes the selected design into a real work. The creation of the work begins with pattern making, scratching, batik, coloring, sewing, sewing and finishing. The results of the creation of this work are 4 casual outfits, each of which has a title and philosophical meaning implied in each motif, namely work 1 with the title Bahuwirya, work 2 with the title Casugraha, work 3 with the title Laksana, work 4 with the title Dianti. By creating clothing that features eucalyptus plant motifs, people can grow a sense of love and pride in having a plant that has many benefits.